2021
DOI: 10.1002/agj2.20938
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between soil carbon and nitrogen, soil properties, and dryland crop yields

Abstract: Soil organic carbon (SOC) is an important indicator of soil health, but its analysis requires a two-step process of measuring soil total carbon (STC) and inorganic carbon (SIC) in arid and semiarid regions. Determination of STC or soil total nitrogen (STN) for SOC can shorten the analytical process, which may be used for measuring soil health. We related STC, STN, SOC, and SIC to 62 soil properties and mean crop yields across years in two long-term (14-and 36-yr-old) experiments in the northern Great Plains. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The STC and STN stocks at 0–120 cm were calculated by adding stocks from individual depth layers. Because STC related similar to or better than SOC with most soil properties and crop yields (Sainju et al., 2021), we used STC instead of SOC to observe changes in C and N stocks under perennial grasses in the semiarid region. Measurement of STC also saves time and cost of analysis because it requires only one‐step of determination compared to SOC which requires two‐step processes of measuring STC and SIC (Sainju et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The STC and STN stocks at 0–120 cm were calculated by adding stocks from individual depth layers. Because STC related similar to or better than SOC with most soil properties and crop yields (Sainju et al., 2021), we used STC instead of SOC to observe changes in C and N stocks under perennial grasses in the semiarid region. Measurement of STC also saves time and cost of analysis because it requires only one‐step of determination compared to SOC which requires two‐step processes of measuring STC and SIC (Sainju et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…We chose soil total C (STC) instead of SOC to measure C sequestration rates under perennial bioenergy crops in dryland farming in the semiarid climatic condition of the US northern Great Plains because STC was equally sensitive to management practices, associated with more soil properties, and related better with crop yields than SOC (Sainju et al., 2021). As dryland soils contain significant amount of soil inorganic C (SIC) mainly in subsoil layers where the potential for C sequestration is greater, using STC to measure C sequestration rate is more meaningful than using SOC, especially in dryland cropping systems in arid and semiarid regions (FAO, 2004; UNEP, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation analysis revealed that SAN positively correlates to FWC, TOC, SAP, and SAK. The positive correlations between SAN with FWC (Zhang and Wienhold 2002) and TOC(Sainju et al 2021) are well known. However, category-wise analysis revealed that such current study, most of the Coconut-growing soils (58%) showed a high level of SAP in the elds.Among the soil orders, Ultisols (77.77%) and Entisols (57.46%) showed a signi cantly increased level of available phosphorus than others.…”
mentioning
confidence: 95%